P193 THE DEVELOPMENT OF AN IBD SPECIALTY CLINIC WITHIN A GASTROENTEROLOGY PRACTICE. (18th January 2018) - Pure, Natalie; Mize, Carrie
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic disease that has no cure. Patients with inflammatory bowel disease often require frequent hospital visits due to rapid changes in their illness. After analyzing the amount of hospital visits the practice's IBD patients were making on a yearly basis, it was apparent that these patients needed rapid access to care, provided by a Gastroenterologist. It was then decided to develop an IBD clinic within the Gastroenterology practice for these patients to receive high quality, affordable, and quick access to care. Method: The first step in developing the IBD clinic was designating a group of physicians to offer same day appointments to patients needing to be seen for flares. This allows patients to bypass the emergency room and be seen directly by a GI specialist. The next step was hiring a nurse navigator to triage the calls of sick patients and facilitate the movement of patients throughout the IBD clinic. The final step in developing the IBD clinic was to establish a telephone number for IBD patients to call in order to be triaged quickly. Results: By opening an IBD clinic it has been found that patients are requiring less hospital visits, missing less work, and achieving an acceptable form of remission of their chronic illness. The patients are also more satisfied with the care they receive because there is less wait time compared to an emergency room setting. The patients feel as though their illness is treated as a priority and that they are treated more efficiently since they are seeing is an actual GI specialist. Conclusion: Since the IBD clinic has been offered to patients our practice has cut emergency room referrals to the emergency room by approximately 70%. Emergency room referrals are being saved for those patients that need an inpatient setting. The IBD clinic has improved the overall satisfaction of our patients and decreased the cost of their healthcare due to chronic illness tremendously.